Nanosecond illumination source for speckle-free liquid crystalmicroscopy. Issue 4 (16th March 2021) - Ryzhkova, A. V.; Jagodič, U.; Muševič, Igor
ABSTRACT: We present a setup for the speckle-free, low-light microscopy imaging at 5 ns exposure times. The design is based on stroboscopic principle and uses fast and incoherent fluorescent emission from a dye, excited by a picosecond laser pulse. The basic spatial, spectral, and temporal beam properties are characterised, modelled and compared for two different designs of the source: (i) Rhodamine 6 G dye dissolved in ethanol and put in a glass cuvette, and (ii) random laser based on the dispersion of 300 nm TiO2 nanospheres in an ethanol solution of Rhodamine 6 G dye. The proposed solution of Rhodamine 6 G dye in ethanol put in a glass cuvette gives an excellent image quality with high contrast, excellent stability and tunable coherence. It delivers 30 nJ of completely incoherent light per excitation laser pulse energy of 40 μ J. It allows for the photographic measurements with 5 ns exposure time, demonstrated in imaging of thermally quenched 5CB liquid crystal. The set-up is used in studies of Kibble-Zurek mechanism of topological defect nucleation and growth at sub-microsecond time resolution and extremely fast cooling rates of 40, 000 K/s. GRAPHICAL ABSTRACT: